Effects of phenotyping environment on identification of quantitative trait loci for rice root morphology under anaerobic conditions - Kamoshita, A.; Zhang, Jingxian; Siopongco, J.; Sarkarung, S.; Nguyen, H.T.; Wade, L.J. (Wiley, 2002)
In the rainfed lowlands, rice (Oryza sativa L.) develops roots under anaerobic soil conditions with ponded water, prior to exposure to aerobic soil conditions and water stress. Constitutive root system development in anaerobic soil conditions has been reported to have a positive effect on subsequent expression of adaptive root traits and water extraction during water stress. We examined effects of phenotyping environment on identification of quantitative trait loci (QTLs) for constitutive root morphology traits using 220 doubled‐haploid lines (DHLs) from the cross of ‘CT9993‐5‐10‐1‐M’ (CT9993; japonica, upland adapted) × ‘IR62266‐42‐6‐2’ (IR62266; indica, lowland adapted) in four greenhouse experiments. Broad sense heritability (h 2) was 75, 60, and 64% on average for shoot biomass, deep root morphology, and root thickness traits, respectively. Quantitative trait loci analysis identified 18 genomic regions associated with deep root morphology traits, but only three were identified consistently across experiments. Three out of a total of eight QTLs for root thickness traits were found in more than one experiment. The maximum genetic effects caused by a single QTL were increments of 0.05 g of deep root mass below a 30‐cm soil depth, 0.9% of deep root ratio, 1.6 cm of rooting depth, and 0.09 cm of root thickness, with phenotypic variation explained by a single QTL ranging from 6.8 to 51.8%. The results demonstrate the importance of phenotyping environment and suggest prospects for selection of QTLs for deep root morphology, root thickness, and vigorous seedling growth under anaerobic conditions to improve the constitutive root system of rainfed lowland rice. There was some consistency in QTL regions identified, despite the presence of QTL × environment interactions.